Initial assessment of the Express Connect bus program - Kho, Jeremy Aaron T.
Launched by DOTC, MMDA, and LTFRB, Express Connect is a bus program that aims to convince private car owners to shift to public transport. The express bus service reportedly reduces travel time by reducing the stops made between major junctions, particularly Fairview, Ortigas Avenue, Ayala Avenue, LRT 1 Buendia station, and Roxas Boulevard. This study aims to assess the program by identifying its demand profile, determining travel time savings, and characterizing operational patterns. However, the scope is limited to characteristics pertaining to the passengers and not the bus operators. Three surveys are constructed, namely boarding and alighting surveys, travel time surveys, and passenger interview surveys. On-board surveys are contracted for two midweek days, the 29th of April and 5th of May 2015, and one Saturday, the 2nd of May 2015, covering the AM and PM peak and off-peak periods. The respondents of Express Connect tend to be younger and of lower income than those of conventional services, which had more diverse respondents, indicating maturity in their market. However, 71% to 78% of modal shifts are from conventional buses, with private cars registering a 1% share. Although occupancies of express buses are lower than conventional buses during the weekday, they are similar during Saturdays. Trip distribution analysis shows that at least 22% of conventional bus respondents have origins and destinations suitable to the long-haul express service, implying that express bus occupancies have potential to expand. Travel time reductions are confirmed, with the trip Fairview to Ayala Avenue meeting and surpassing the expected saving of 30 minutes. Boarding and alighting patterns validate the prescribed stops for Express Connect, but identify another major stop in Cubao. Based on the study results, the information campaign has not penetrated all sectors of the market and would do well to readjust its strategy to target current conventional bus users, instead of private car owners.